Optimalisasi Tong Sampah sebagai Teknologi Tepat Guna pada Wisata Padepokan Lembah Sumilir: Pembuatan Dan Pemanfaatan Teknologi Tepat Guna Tong Sampah Pada Objek Wisata Padepokan Lembah Sumilir - Ikaningtyas, Maharani; Achmad himawan, Shendy (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
Garbage is a shared problem that has not been resolved to date. This waste problem occurs at the tourist spot Padepokan Lembah Sumilir, Wonosalam Village, Wonosalam District, Jombang Regency. The results of previous observations found that in the Sumilir Valley Padepokan tour there were problems faced, namely the problem of waste management. Therefore, the solution that can be offered is to create a waste management system called a Waste Bank based on appropriate technology (TTG). The result of this activity is to make trash cans so that tourists can dispose of trash in its place according to the type of waste that is there